Eficacia antibacteriana in vitro de marco (Ambrosia arborescens Mill.) y paico (Chenopodium ambrosioides L.) en una formulación cosmética - Ibarra Martínez, Marco Vinicio (2013)
The aim of this study is to evaluate the in vitro antibacterial activity of Ambrosia arborescens Mill. and Chenopodium ambrosioides L. in a cosmetic formulation. To carry out this investigation, the first step was to perform the quality control of drugs and later, to get the essential oil of Chenopodium ambrosioides L. by steam distillation and to get the soft extract of Ambrosia arborescens Mill., by percolation. The test of disc diffusion sensitivity was performed by the use of different concentrations of essential oil and soft extract against: Staphylococcus aureus ATCC 12600, Staphylococcus epidermidis ATCC 14990, Pseudomonas aeruginosa ATCC 19429 and Escherichia coli ATCC 11229.